The effectiveness of zakat assistance towards straightening religiosity of Muslim converts (Muallaf) / Mohammad Syukri Jalil ... [et al.] - Jalil, Mohammad Syukri; Abdul Ghafar, Mohd Sabri; Awang, Azaruddin; Yusoff, Murni (Academy of Contemporary Islamic Studies (ACIS), 2022)
Straightening religiosity of Muslim Converts (muallaf) is an important element especially involving zakat assistance. This is due to the fact that, the zakat assistance is still importance allocation to muallaf. Thus, there are among muallaf who do not understand the faith of Islam well. As a result, there are among muallaf feel they are marginalized after embracing Islam. This is due to the lack of attention from the relevant parties such as zakat in helping them especially involving spiritual and physical assistance. The objective of this article to identify the factors straightening that influence the level of religiosity among muallaf through zakat. The methodology of this study is through the method of the library regarding articles and reports, conceptual and based on literature research. This finding will support continuous development with the aid of muallaf to straightening the religiosity through zakat assistances. There are two factors influence the straightening religiosity among muallaf, It hoped that with the success of zakat assistances toward muallaf will be produce quality for religion and avoided negative perception of public among muallaf.